“WHAT DOES THE BARRIERS OF BEING A LAYPERSON IN COMMUNITY AND MENTAL HEALTH MEAN?” A PHENOMENOLOGICAL APPROACH - Dedi Kurniawan; Galuh Kumalasari; Frastiqa Fahrany; Hardiyanto Hardiyanto; Ratna Roesardhyati (Indonesian Journal of Health Care Management, 2021)
The treatment of mental health problems has changed over from hospitalbased to community-based psychiatric services. They focused not only on medication but also emphasized more on prevention and promotion. This strategy was carried out not only by health workers but also by laypersons from community empowerment. Laypersons have experienced difficult conditions and problems, such as the possibility of experiencing role conflict, fatigue, physic, and verbal abuse. Those a challenge and pressure that often affects laypersons as a pioneer of the mental health community. The purpose of this study was to explore the barriers of laypersons in the mental health community in Malang, Indonesia. The research design used was qualitative with an interpretive phenomenological approach. The data collecting using indepth interviews with semi-structured interview guides involving twelve laypersons who participated in this study. Laypersons were interviewed individually and asked this single question: What does the barriers experience of being a layperson of community mental health empowerment mean? Participant's descriptions were analyzed using Interpretive Phenomenology Analysis (IPA). Six categories emerged from data analysis: (i) moral and material community support; (ii) limited facilities and infrastructure; (iii) sense of belonging; (iv) feel exploited; (v) sense of purpose and (vi) tough. The findings suggest that each individual has unique barriers’ experiences of being laypersons in the community. In conclusion, the layperson's lack of motivation and sense of responsibility was a big barrier to improving mental health services in the community, it's tougher when they have less support from all community sectors.